Effect of applying the specific situation theory on the quality of life in patients with heart failure - Marzieh Sadeghizadeh; Behnaz Bagherian; Hamed Vahidi; Sakineh Sabzevari (Tehran University of Medical Sciences, 2021)
Background & Aim: Self-care education is one of the effective ways to improve the quality of life and health in patients with heart failure. The purpose of this study was to determine the effect of applying the specific situation theory on the quality of life in patients with heart failure. Methods & Materials: In a clinical trial study, 80 patients with class 2 or 3 heart failure, referred to 12 Farvardin hospital in Kahnooj in 2018 were included. Data collection tool included a three-part questionnaire: demographic variables, Left Ventricular Dysfunction Scale to assess patientschr('39') quality of life, and Self-care Heart Failure Index. The questionnaires were completed at the first visit and three months after follow-up. Data was analyzed using independent and paired t-test, ANOVA, Pearson correlation through the SPSS software version 20. Results: Before the intervention, there was no significant difference in the scores of quality of life and self-care between the two groups. After the intervention, the mean score of quality of life and self-care dimensions increased (P<0.001). Regarding self-care after the intervention, the highest score was related to self-care confidence with mean and standard deviation of 21.43 and 3.30 respectively, and the lowest score was related to self-care management with mean and standard deviation of 17.45 and 5.5 (P<0.001). Conclusion: Paying attention to the dimensions of self-care based on a specific situation theory can lead to a better understanding of these patients' problems and appropriate planning, and in turn improvement of the quality of life. Since in this study, most of the participants were illiterate, using visual teaching aids, adjusting the schedule according to the patientchr('39')s conditions and readiness, and if necessary, family involvement can have positive results. It appears necessary to consider the underlying factors in the implementation of self-care programs, especially in people with lower levels of education and income. Clinical trial registry: IRCT20141109019862N6